ПРОБЛЕМЫ И МЕТОДИЧЕСКИЕ РЕШЕНИЯ ПРИ ПРЕПОДАВАНИИ ИНОСТРАННЫХ ЯЗЫКОВ ТЮРКОЯЗЫЧНОЙ АУДИТОРИИ - Абдуллаева, Р.А.; Джуманиязова, Н.А. (SCIENCE and SOCIETY, 2025)
The article discusses the linguistic, psycholinguistic and methodological features of teaching Russian and English to representatives of Turkic-speaking peoples.